Internalization of Prophetic Character in the Congregation of Majlis Maulid wa al-Ta'lim Riyadlul Jannah in Malang (Living Hadith Study) - Yaqin, Mokhammad Ainul; Sumbulah, Umi; mulyono, Mulyono; Barizi, Ahmad (International Journal Labs, 2024)
This research explores the phenomenon of ta'lim and salawat through Majlis Maulid wa al-Ta'lim Riyad al-Jannah as an embodiment of the concept of living hadith which functions to emulate the da'wah of the Prophet PBUH. Observation, interviews, and documentation were carried out in the ta'lim assembly, while condensation analysis, data presentation, and triangulation techniques were used for data validation. The results of the study reveal several main points: 1) The concept of prophetic character formation is based on the Qur'an, hadith, culture, and liberation-transcendent humanist values; 2) Salawat hadith is the basis for worshippers to salawat as a form of prayer for blessings and peace of life; 3) The implementation of prophetic character formation is carried out through three paths: the formation of an understanding of prophetic values, the habituation of prophetic values through culture, and the development of discipline; 4) The implications of the formation of prophetic character result in individual transformation (personal change) and social (active in religious, environmental, and community activities). This transformation also has an impact on the taklim council as a universal holistic education base.